Disease of the Year 2019: Ocular Toxoplasmosis in HIV-infected Patients (2020)
Ocular toxoplasmosis (OT) may be an initial manifestation of acquired immunodeficiency syndrome (AIDS) in human immunodeficiency virus (HIV)-infected patients. OT has different clinical manifestations and can mimic other intraocular infections. Clinical findings may show single or multifocal retinochoroidal lesions or panuveitis. Atypical presentations are associated with extensive uni- or bilateral areas of retinal necrosis. OT lesions not associated with preexisting retinochoroidal scars are usually due to acquired rather than congenital infection. When CD4+ T cell counts are less than 100 c/uL, vitritis is frequently mild. Isolated anterior uveitis has been reported in single cases. Positive immunoglobulin M (IgM) antibodies are rare but their presence can support the diagnosis. As atypical presentations of OT are common, anterior chamber puncture for multiplex polymerase chain reaction amplification of infectious DNA should be considered, as early diagnosis and treatment can prevent massive tissue destruction and preserve vision. This review provides an overview of OT in HIV–infected patients. © 2020, © 2020 Taylor and Francis Group, LLC.